Mykola Voronyi: autobiography in the genre form of letters (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
Mуkola Voronoy memoir works are represented by a letter to I. M. Lyzanivskiy who had to help O. I. Biletskiy to write a foreword to the publication of the poet. By genre it is a letter – autobiography of subjective type, rather lengthy, written candidly and emotionally. The product provides the ability to trace the ideological and creative evolution of the writer, his work in theater and literature.
Keywords: memory; memoirs; autobiography; letter; subjective type